Characteristics of Complex Regional Pain Syndrome in Patients Referred to a Tertiary Pain Clinic by Community Physicians, Assessed by the Budapest Clinical Diagnostic Criteria. Issue 11 (23rd October 2014) - Mailis‐Gagnon, Angela; Lakha, Shehnaz Fatima; Allen, Matti D.; Deshpande, Amol; Harden, Robert Norman
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to describe the characteristics of patients referred with complex regional pain syndrome (CRPS) diagnosis to a tertiary care pain center. Method Descriptive chart review study of all patients referred by family physicians or community specialists as having CRPS (2006–2010). Data extraction included demographics, pain ratings, and diagnosis utilizing the Budapest CRPS criteria. Results The study population consisted of 54 subjects (male [M] = 7, female [F] = 47). Only 27.7% were classified as CRPS by the clinical expert. Four additional subjects carrying other diagnoses but found to have CRPS were added to the analysis. The non‐CRPS group consisted of 39 subjects (M = 8, F = 31) and the CRPS group of 19 (M = 2, F = 17). CRPS patients were statistically significantly more likely to 1) have suffered a fracture; 2) report symptoms in each of the four symptom categories, as well as signs in three or four categories collectively; and 3) have allodynia/hyperalgesia alone or in combination (85/90%) as compared with the non‐CRPS group (23/25%, respectively). The non‐CRPS group was much more likely to report no symptoms or signs at all in the different symptom and sign categories. Of the 39 non‐CRPS patients, 74% had other diagnosable entities (1/3 suffering from specific neuropathic pain conditions, e.g., radiculopathy, diabetic neuropathy, etc. and 2/3 from discreet musculoskeletal entities), while 18% were diagnosed with psychogenic pain disorders including conversion reaction associated with immobility or paralysis. Discussion Besides fulfilling the Budapest CRPS diagnostic criteria, the most important other factor for diagnosing CRPS is the exclusion of a neuropathic, musculoskeletal, or non‐biomedical condition accounting for the presentation.